Análisis de emergencias tecnológicas con sustancias químicas empleando emerquim. (2022)
In order to carry out an analysis of the chemical technological accidents that occurred in the period 2015 to 2019 reported to CISPROQUIM, the following is created investigative document. The total number of accidents reported during this period was of 266 emergencies - technological chemical being the year 2015 the one with the most emergencies reported in this period with 83 reported emergencies, of which the Most of the reports occurred in Bogotá and the year with the fewest emergencies technological with chemical product involved presented according to this information is the year 2019 with 38 cases.